PENGEMBANGAN MEDIA DAKON PADA PEMBELAJARAN MATEMATIKA UNTUK SISWA SEKOLAH DASAR - Aliyah, Ana Imroatul; Dwi Rochmania, Desty (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
This study aims to develop the dakon media as a learning aid for teaching FPB dan KPK materials to elementary school students. Dakon media was chosen because of its potential to make learning more interactive and enjoyable, thus enhancing students understanding of mathematical concepts that are often considered difficult. The development of this mathematical dakon media uses the Borg and Gall Research and Development (R&D) model. There are 10 steps: identifying potentials and problems, collecting information, product design, design validation, design revision, product trial, product revision, usage trial, final product revision, and mass production. The needs analysis results indicate that students have never used dakon media in mathematic learning, and the absence of suitable media makes it difficult for them to understand the concepts of FPB dan KPK. The developed dakon media was validated by subject matter experts and media experts to ensure its feasibility as a learning tool. Product testing was conducted on fourth grade students at SDN Sukosari Jogoroto. The results of the mathematical dakon media development showed that the percentage obtained from media expert validators was 94,12%. The percentage result from subject matter expert validators was 88,33%, furthermore, the teacher trial result was 91,34%. A small group trial was conducted with 5 students, resulting in a percentage of 92,69%, while the fields trial conducted with 15 students yielded a percentage of 93,58%. Based on the overall data analysis, it can be concluded that the development of mathematical dakon media is suitable for use as a mathematics learning tool in elementary schools.